2020
DOI: 10.1186/s41235-020-00253-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of team preferences on soccer offside judgments in laypersons: a quasi-experimental study

Abstract: The present study uses a quasi-experimental design to investigate the impact of team preferences on the accuracy of offside judgments. In Experiments 1 and 2, supporters of two German soccer clubs (i.e., Borussia Dortmund and FC Schalke 04) judged offsides in artificial scenes from a match between the clubs. We expected that supporters of both clubs would less frequently report the offside position of a forward from the preferred team. The results of Experiment 1 partly confirmed the predictions. Both groups r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The present study tested the hypothesis that different shirt colors, which are presumably associated with different figure-background contrast, affect the number of offside judgments against a particular team. In a previous laboratory study, Wühr et al [ 10 ] observed more offside judgments for forwards wearing the outfit of Schalke 04 (blue shirts, white shorts) than for forwards wearing the outfit of Borussia Dortmund (yellow shirts, black shorts), when the figure-background luminance contrast was higher for Schalke 04 than for Borussia Dortmund. Here, we asked whether a similar pattern would occur in real matches of the German Bundesliga.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study tested the hypothesis that different shirt colors, which are presumably associated with different figure-background contrast, affect the number of offside judgments against a particular team. In a previous laboratory study, Wühr et al [ 10 ] observed more offside judgments for forwards wearing the outfit of Schalke 04 (blue shirts, white shorts) than for forwards wearing the outfit of Borussia Dortmund (yellow shirts, black shorts), when the figure-background luminance contrast was higher for Schalke 04 than for Borussia Dortmund. Here, we asked whether a similar pattern would occur in real matches of the German Bundesliga.…”
Section: Discussionmentioning
confidence: 99%
“…Because attention is biased towards higher-contrast stimuli (e.g., [ 16 , 17 ]), ARs will more often “find” the higher-contrast player (in a blue shirt) than the lower-contrast player (in a yellow shirt), and therefore the bias would increase offside judgments against Schalke 04, and decrease offside judgments against Borussia Dortmund. Of course, this account must be taken with caution because we have not measured figure-background contrast in the matches included in our studies, but we know that higher figure-background contrast can increase the number of offside decisions against the more salient team from previous laboratory studies ([ 10 ]). Hence, we can provide indirect empirical evidence for our account.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations